The Effect of Work Ethics and Work Environment on Employee Performance At The Jakarta Primary Tax Service Gambir Tiga - Munir Azhari; Harries Madiistriyatno; Sukar Naibaho (PT. Publikasiku Academic Solution, 2023)
This research is quantitative, descriptive, and associative type. The population in this study was 70 employees at the Gambir Tiga Jakarta Primary Tax Service Office. The sampling technique in this study is total sampling. With the total sampling technique, a sample of 70 employees was taken at the Gambir Tiga Jakarta Primary Tax Service Office as respondents in this study. The results of this study indicate that: 1) There is an influence of work ethic on employee performance, as evidenced by the count for the X1 variable (Work Ethic) of 13,491, while the value of the t table for n = 70 is 1,994. So t arithmetic> table or 13,491> 1,994, it can be concluded that the Work Ethic variable influences partially the Job Performance of Employees. The coefficient regression value of the. The work ethic variable (X1) to the Employee Job Performance variable (Y) is 0.405. This means that if the Work Ethics variable (X1) rises by 1 unit it will increase the. Employee Job Performance (Y) variable by 0.405, assuming the Work Ethics variable (X1) is considered constant. 2) There is an influence of the work environment on employee work performance, as evidenced by the count for the X2 variable (Work Environment) of 16,862, while the value of the table for n = 70 is 1,994. So tcount>table or 16,862>1,994, it can be concluded that partial Work Environment variables affect Employee Work Performance. The value of the regression coefficient of the Work Environment variable (X2) to the Employee Job Performance variable (Y) is 0.605. This means that if the Work Environment variable (X2) increases by 1 unit, it will increase the Employee Job Performance (Y) variable by 0.605, assuming the Work Environment variable (X2) is considered constant. 3) There is an influence of work ethic and work environment together on employee work performance, as evidenced by the ANOVA or Ftest or Fcount test in the value of 302,319 which is greater than Ftable of 2.74 with a significant level of 0,000 because 0,000 <0.05, so it can be said that the Work Ethics variable (X1) and Work Environment variable (X2) together influence the Employee Performance variable (Y). While the Adjusted R. Square value of 0.900. This shows that 90% of the work ethic and work environment simultaneously (jointly) affect employee work performance, while the remaining 10% is influenced by other factors not examined in this study.